Accentuation in Dictionary of Foreign Words and Accentual Manual of Adolf Blatoljub Klaić in Comparison with the School Dictionary of Croatian Language - Domagoj Vidović (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2014)
On the basis of declensions of monosyllabic o-stem nouns the author compares the accent types in Klaić’s Dictionary of Foreign Words and orthoepic manual with the School Dictionary of the Croatian language (Institut za hrvatski jezik i jezikoslovlje and Školska knjiga). These works have in common the adherence to the Neoštokavian accent rules as well as the tendency to systematize accentuation. They differ in the selection of some accent types, which are in Klaić’s works based on older language manuals and dialectological data while in The school Dictionary they are based on the study of accent paradigms. The author shows that Klaić’s contribution to the systematization of accentuation in Standard Croatian would have been considerably greater if his manual were published at the time it was written. The author also shows the differences in the accentuation of certain words in contemporary Croatian dictionaries which are partly due to the lack of orthoepic manuals and the nonawareness of the existence of an accent system as well as the selective deviations from the accent system.